1988
DOI: 10.7326/0003-4819-109-11-855
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of the Central Nervous System by Treponema pallidum: Implications for Diagnosis and Treatment

Abstract: Central nervous system invasion by T. pallidum is common in early syphilis, and is apparently independent of HIV infection. Examination of the CSF may be beneficial in patients with early syphilis, and therapy should be guided by knowledge of central nervous system involvement. Conventional benzathine penicillin G therapy may have reduced efficacy in patients with early syphilis who are also infected with HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
254
0
28

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(287 citation statements)
references
References 31 publications
5
254
0
28
Order By: Relevance
“…It has been reported that the reduction in the titer of serological tests after treatment among HIV-co-infected patients may be slower (10); however, HIV infection in the present case was reconfirmed to be negative at that time, and so we postulated the presence of some obstinate focus. Because CNS involvement can occur during any stage of syphilis (11), and CSF evaluation is recommended in those who experience treatment failure (12), we performed lumbar puncture, considering the possibility that T. pallidum had already invaded his CSF before the first therapy with AMPC, and that the pathogen which was not eradicated by the therapy might lie hidden in CSF and resurge gradually. Because AMPC cannot reach the CSF at a sufficient concentration to eradicate all T. pallidum, AMPC alone was thought to be insufficient to treat neurosyphilis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the reduction in the titer of serological tests after treatment among HIV-co-infected patients may be slower (10); however, HIV infection in the present case was reconfirmed to be negative at that time, and so we postulated the presence of some obstinate focus. Because CNS involvement can occur during any stage of syphilis (11), and CSF evaluation is recommended in those who experience treatment failure (12), we performed lumbar puncture, considering the possibility that T. pallidum had already invaded his CSF before the first therapy with AMPC, and that the pathogen which was not eradicated by the therapy might lie hidden in CSF and resurge gradually. Because AMPC cannot reach the CSF at a sufficient concentration to eradicate all T. pallidum, AMPC alone was thought to be insufficient to treat neurosyphilis.…”
Section: Discussionmentioning
confidence: 99%
“…Initially recognised in the pre-antibiotic era 39 and reported early in the penicillin era, 40 several more recent case studies report neurorelapse occurring in HIV-infected patients. 19,[41][42][43][44][45] While it is difficult to rule out the possibility of reinfection entirely in these case reports, it has also been hypothesised that neurorelapse may be more common in HIV-infected patients with syphilis because benzathine penicillin G, the usual treatment for uncomplicated syphilis, does not clear T. pallidum from the CNS, the eye or the inner ear 46,47 and HIV impairs cell-mediated immunity, allowing T. pallidum to persist at these sites. 41 Further systematic studies are needed to determine whether HIV co-infection truly increases the odds of neurorelapse with syphilis.…”
Section: Neurorelapse: Neurological Complications After Syphilis Treamentioning
confidence: 99%
“…Então, o diagnóstico depende dos testes sorológicos e do exame do LCR. 6,7,20,22 É descrito que a análise liquórica pode ser benéfica em portadores da sífilis primária. 21 Estudos avaliando portadores de sífi-lis latente ou de duração desconhecida observaram VDRL positivo no líquor, confirmando neurolues entre 16,2 e 21% dos doentes.…”
Section: Introductionunclassified
“…17,23,24 E o agente foi isolado no líquor de 30% dos doentes de sífilis primária ou secundária não tratados. 22 Entretanto, a neurolues é improvável quando o VDRL sérico estiver negativo. 14 Nesses casos, a punção do líquor não é recomendada.…”
Section: Introductionunclassified